TRICHOBEZOAR AND ITS SURGICAL MANAGEMENT IN A DOG - Shafiuzama, Mohd; Simon, M Shiju; Sooryadas, S; Kumar , R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A seven-year old male Dachshund weighing 10 kg was presented with the history of depression, anorexia, frequent emesis and obstipation for the past two days. Abdominal palpation revealed a palpable sausage shaped mass inside. Radiographic studies revealed outflow obstruction of the intestine. Under general anaesthesia, a trichobezoar - at the level of distal duodenum and proximal jejunum, was removed through a mid-ventral celiotomy.